The Application of Vinay and Darbelnet Model to English and Urdu Translations of Surah Ad- Duha: A Comparative Study - Hadiya Ahmed Hani; Tayyaba Zainab (English Lecturers and Teachers Association (ELTA), 2024)
This study aims to analyze the linguistic features of three translated versions of Surah Ad Duha with the help of Vinay and Darbelnet's translation theory.The analysis is based on the seven translation procedures proposed by Vinay and Darbelnet, which include transposition, modulation, equivalence, adaptation, borrowing, literal translation, and oblique translation.The study examines the translators approach which reveals the original linguistic and cultural choices made by the translators to convey the intended message. The study provides tactics of understanding and translating religious texts keeping in consideration the differences in linguistic and cultural features, the use of rhetorical devices, sentence structures, and word choices, and how they contribute to the overall meaning and message of religious textsfor distinct audience. The findings of this research can be used to enhance the understanding of the linguistic and literary aspects of the Qur'an, as well as provide insights into the translation of religious texts. Keywords: Surah Ad Duhaa; VinayDarnelnet model; Direct and Oblique method